2020
DOI: 10.3390/genes11101194
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Structure of the Wild Boar (Sus scrofa) in the Carpathian Basin

Abstract: In the Carpathian Basin the wild boar (Sus scrofa) belongs among the most important game species both ecologically and economically, therefore knowing more about the basics of the genetics of the species is a key factor for accurate and sustainable management of its population. The aim of this study was to estimate the genetic diversity and to elucidate the genetic structure and location of wild boar populations in the Carpathian Basin. A total of 486 samples were collected and genotyped using 13 STR markers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…In congruence with our results, analogous studies on wild boar population structures at the landscape scale found no genetic differentiation resulting from motorway separation [29,78,79], with fencing since 2004 [29] and with >20,000 average users/day [29,78]. It was suggested that genetic clustering effects were rather due to isolation-by-distance [30], or to the species' characteristics or recolonization history [31].…”
Section: Population Differentiationsupporting
confidence: 88%
See 1 more Smart Citation
“…In congruence with our results, analogous studies on wild boar population structures at the landscape scale found no genetic differentiation resulting from motorway separation [29,78,79], with fencing since 2004 [29] and with >20,000 average users/day [29,78]. It was suggested that genetic clustering effects were rather due to isolation-by-distance [30], or to the species' characteristics or recolonization history [31].…”
Section: Population Differentiationsupporting
confidence: 88%
“…On the one hand, it was shown that motorways in Belgium and Lithuania did not represent a significant limitation to gene flow (i.e., migration between regions with successful reproduction) [28,29]. Two studies suggest that most of clustering effects were due to characteristics and recolonization history of the species [30], or to the isolation-by-distance [31], rather than to the landscape features or the urbanization coverage. On the other hand, a Sardinian study highlighted the clustering's effect caused by a quasi-impervious motorway, and to a lesser degree, by urbanized and cultivated areas [32].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used molecular markers are microsatellites (short 2–5 base-pair, repeating sequences of DNA) due to their high polymorphism and possibility of amplification from a small amount of tissue [ 23 , 24 , 25 ]. As in the case of other species [ 26 , 27 , 28 , 29 ], sets of microsatellite markers for the root vole have been developed and tested [ 23 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the study of wild boar genetics is now receiving much attention, both in Russia and other countries (Gladyr et al, 2009;Zinovieva et al, 2013;Rębała et al, 2016;Mihalik et al, 2020). In addition, due to constant outbreaks of the African swine fever (Pestis africana suum) in Russia, the wild boars are regularly shot as potential carriers of this disease.…”
Section: Introductionmentioning
confidence: 99%